Insurance Intermediaries - Ioana Nely MILITARU (CECCAR Business Review)

(untitled)
The insurance contract is concluded between the insured and the insurer. However, insurance relations may also involve other persons than the insured and the insurer, for example, the insurance contractor, the beneficiary, the person covered by the insurance, coinsurers, reinsurers, intermediaries who mediate the conclusion of the insurance contract, etc. This article presents insurance intermediaries. They do not become parties to the insurance contract, although they mediate its conclusion. Insurance intermediaries initiate or carry out insurance distribution activities in exchange for remuneration.